Digital therapeutics in Korea: current status, challenges, and future directions – a narrative review - Hee Jun Shin; Ik Tae Cho; Wan Suk Choi; Hong Rae Kim; Min Bong Kang; Won Jong Yang (Journal of Yeungnam Medical Science)
Digital therapeutics (DTx) are emerging as a transformative innovation in healthcare offering evidence-based digital interventions for the treatment, management, and prevention of various diseases and disorders. In Korea, DTx have gained significant attention as potential solutions to the increasing burden of chronic diseases and mental health conditions. However, the Korean DTx market faces several challenges that hinder its widespread adoption and integration into the national healthcare system. This study provides a comprehensive analysis of the current state of the DTx market in Korea, identifies the key challenges impeding its growth, and proposes strategies for overcoming these obstacles. This study utilized a literature review and market analysis approach to examine the latest research, industry reports, and regulatory documents related to DTx. The analysis focused on three primary areas: (1) the current regulatory landscape, (2) technological advancements and challenges, and (3) economic and commercial factors influencing DTx adoption in Korea. A comparative analysis of global regulatory practices was also conducted to identify best practices. The findings revealed that while Korea has made significant strides in supporting DTx development, the market remains in its early stages. The key challenges include underdeveloped regulatory frameworks, issues with data quality and security, and a lack of established reimbursement pathways. We recommend developing tailored regulatory frameworks for DTx, enhancing policy support for small and medium-sized enterprises involved in DTx development, and increasing investments in technological infrastructure. By addressing these challenges, Korea could position itself as a leader in the global DTx market, delivering innovative and effective treatments to enhance patient care and outcomes.